FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN SUAMI DALAM KELUARGA BERENCANA DI WILAYAH PUSKESMAS KECAMATAN PULOGADUNG JAKARTA TIMUR - Willa Follona (Poltekkes Kemenkes Jakarta III, 2017)
The responsibility of men in terms of family planning is very important in the role of family planning programs. However, there is an imbalance in the number of contraceptive participation in female and male FP acceptors. The participation of men is still very low, compared to female. The purpose of this study is to analyze the relationship between husband characteristics seen from the factors of age, education, occupation, ethnicity, religion, income, number of children, also about husband knowledge, attitudes husband and wife / family support, and access to media / participation of husband as KB acceptor. This is across sectional study of 90 husbands chosen purposively in Pulogadung Sub District in September 2016. The results showed that there was a significant positive correlation between knowledge with the participation of respondents as Family Planning acceptors, the higher the knowledge level, the higher the participation of husband as the acceptors of family planning with p value 0.022 (OR = 4,818; 95% CI 1.476 to 15.728). There was a significant positive correlation between attitudes with the participation of respondents as familyplanning acceptors, the higher the attitudes they have, the higher the participation of husbands as the acceptors of family planning p value 0,007 (OR = 13,813; 95% CI 2,286 to 66,111). Health workers are expected to further promote the promotion of male KB acceptor services, through the provision of family planning education in the form of counseling and family approaches concerning the importance of family planning for men. For those have become acceptors are expected to be role models by spreading to their peer.